Evaluation of Grazing Options During Summer for Growing Heifers – Year 3 - Jaymelynn K. Farney; Kloey Rash; Noelle Collins; Emily Black; Hailey Gillespie (Kansas Agricultural Experiment Station Research Reports, 2024)
Developing methods to provide high quality forage through most of the year is important for cattle operations. The purpose of this study was to determine forage management options to offset the summer “slump” with fescue. Three grass pasture treatments (8 pastures total; 4 acres each) were used in a completely randomized design and stocked with growing heifers (n = 32; initial weight 559 ± 20 lb). Pasture treatments consisted of crabgrass (CRAB), bermudagrass (BERM), and sorghum-sudan interseeded into novel fescue (SS-FES). Novel fescue is fescue variety that has endophyte organism but does not produce toxin. Heifers were weighed and grazed pastures from May to October (150 d). All other pastures were rotationally grazed with two paddocks for CRAB and BERM and 3 paddocks for SS-FES. Sorghum-sudan was interseeded into fescue pastures in late May and June. Average daily gain (ADG) for the entire grazing period was not different between pasture systems. Bermudagrass pastures produced the greatest average biomass. Crabgrass pastures produced one of the lowest biomass early in the grazing period, then one of the highest at the end of grazing period. Biomass production results for the SS-FES pastures were very low, except for July when the sorghum-sudan had the greatest forage production.
Keywords: interseeding; forage production; annual forage; perennial forage